Jenis KB - Virna Putri Amelia; Teuku Yudhi Iqbal (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Family Planning (FP) is a government program designed to balance the relationship between population needs and numbers. The purpose and benefits of family planning are to slow population growth, regulate spacing and delay pregnancy, and reduce birth rates. Based on a 2020 report from BKKBN (National Population and Family Planning Board), the coverage of active family planning participants among couples of reproductive age (PUS) was 67.6%, an increase from 63.31% in 2019. Contraceptive services provided include condoms, pills, injections, insertion or removal of implants, insertion or removal of intrauterine devices (IUDs), tubectomy services, and vasectomy services. Most family planning participants prefer short-term contraceptive methods compared to long-term contraceptive methods (LTCM). This pattern occurs every year; however, in terms of effectiveness, short-term contraceptive methods have a lower success rate in preventing pregnancy compared to long-term methods. LTCMs are contraceptives that can be used for a long period (more than two years), and are effective and efficient for spacing births by more than three years or for ending childbearing among couples who no longer wish to have children.. Contraception refers to efforts to prevent pregnancy, which can be temporary or permanent, and is generally divided into traditional methods and modern methods (hormonal and non-hormonal). This program aims to improve the welfare of mothers and children, promote small family structures according to economic conditions, and reduce maternal and infant mortality rates. In addition, the family planning program encourages the use of contraceptive methods to regulate the spacing and number of desired children.